Numerical Simulation of turbulent Flow Over a Cavity - Afridi, Usman (My University, 2012)
Cavity flow and control of these flows have been of great importance for military as well as civil applications. Modern aircraft with internal carriage of weapon require active flow control techniques to ensure the structural integrity by limiting the open bay acoustic resonance and efficient payload deployment. To implement these techniques it is important to understand the flow features and identify the source of resonance. Detached Eddy Simulation(DES) is carried out for subsonic flow (M = 0.85) over a three dimensional cavity with Reynolds number based of cavity length equal to 7 × 106. A good comparison with the available experimental data for the similar configuration validates the DES results. Special attention is paid towards the prediction of unsteady pressure fluctuations and mixing layer and the resulting tonal modes due to their interaction. Furthermore, the instantaneous and mean flow structures inside the cavity are compared with the available Large Eddy Simulation (LES) data, showing a good agreement with slight deviation at the leading edge of the cavity. The Sound Pressure Level (SPL)comparison on cavity floor points show a good match between DES and experimental results and also capturing the tonal modes. The Overall Sound Pressure (OASPL) distribution is slightly overestimated (with maximum difference equal to 1.5dB) by the DES. It is also observed that the self sustained oscillations related to the tonal modes are independent of the stream-wise location in the cavity. The correlation analysis of the cavity floor points reveal that the low frequencies are more correlated to the pressure fluctuations in these locations.
Keywords: Strömningsmekanik; Innovation och entreprenörskap (nyttiggörande); Transport; Fluid mechanics; Innovation & Entrepreneurship; Transport